Quien es tu momia? - Stine, R. L. (New York : Scholastic, 2011)
Abby and Peter visit their Uncle Jonathan, who seems very knowledgable about Egyptian mummies, but they become suspicious about the strange sounds coming from a room inside his house, and their fears continue as they are invited to Horrorland.
4.
8-12.
Accelerated Reader
Accelerated Reader AR
Texto en español.
Keywords: Mummies -- Juvenile fiction; Amusement parks -- Juvenile fiction; Horror tales -- Juvenile literature; Momias -- Novela juvenil; Parques de diversiones -- Novela juvenil; Cuentos populares de terror -- Literatura juvenil